Falls predict cognitive status. (31st December 2021) - Gray, Michelle; Paulson, S.; Gills, J.L.; Glenn, J.M.; Madero, E.N.; Myers, J.; Campitelli, A.; Jones, M.; Vincenzo, J.; Walter, C.
Abstract: Background: Cognitive impairment is associated with increased falls and fall risk among older adults. In fact, studies have significantly predicted falls between high and low cognitive functioning community‐dwelling older adults. However, many negative cognitive changes occur years before significant cognitive changes arise. Thus, the purpose of the present investigation was to determine the ability of falls to predict cognitive status using a digital Digit Symbol task (Neurotrack Technologies, Inc., Redwood City, CA). Method: Sixty‐nine community‐dwelling older adults (80.7 ± 5.4 years) volunteered to complete a falls history questionnaire and a digital Digit Symbol task. Cognitive groups (High [HDS] and Low Digit Symbol [LDS] function) were determined based on age‐sex normative values. Logistic regression analysis was conducted predicting cognitive group placement using age, sex, education, and previous falls within previous 12 months. Result: By knowing the four predictor variables (falls, age, sex, education), cognitive group (HDS vs. LDS) was predicted correctly 80% of the time. Sensitivity and specificity were 90% (37 of 41) and 64% (18 of 28), respectively. The addition of fall risk was not statistically significant; however, it increased sensitivity by 4% and specificity by 13%. Conclusion: The results suggest that knowing falling status may help identify older adults with cognitive impairment, specifically deleterious changes in processing speed. While the mechanisms cannot be elucidated from the present investigation, others have suggested slower processing speed is associated with impaired balance; thus, leading to falls. Future research is needed to further examine the relationship between falls and cognitive performance in hopes that identifying fallers could lead to more extensive cognitive testing.